Proceso de atención de enfermería en adulto mayor con enfermedad pulmonar obstructiva crónica. - Suarez Coello, José Hamburgo (2021)
Chronic obstructive pulmonary disease is a pathology that mainly affects the respiratory system, characterized by inflammation of the bronchial tree causing difficulty in the exchange of air between the external and internal environment, generating respiratory distress in the patient. COPD is a disease that originates as an inflammatory response to constant exposure to toxic inhalants, including those resulting from tobacco use. Currently there are 300 million patients diagnosed with COPD worldwide, with low-income countries having the highest rate of these cases, Latin America has a 13.4% incidence of this pathology, the most frequent stage being mild COPD or moderate. This case study shows the evaluation, diagnosis and treatment of an elderly patient with a medical diagnosis of chronic obstructive pulmonary disease, developing the process of nursing care in the patient, evaluating the clinical evolution of the patient and the effectiveness of the Care Process. of Nursing focused on the deterioration of gas exchange.